Antimicrobial activity of extracts of Byrsonima crassifolia roots - Albarello Gellen, Luis Fernando; Costa Silva, Edgard Henrique [UNESP] (Federal Inst Amapa, Campus Macapa-ifap, 2016)
The Byrsonima crassifolia popularly known as murici is widespread in the North, Northeast and Midwest. Widely used in local cuisine, both for its exotic taste as for its therapeutic effects. The objective was to evaluate the antimicrobial potential of B. crassifolia root extract on bacteria of medical interest. Samples of B. crassifolia were collected within the State of Tocantins, then forwarded to the Centro Universitario Luterano de Palmas - TO, where extracts of production processes from the roots were performed. The other procedures were carried out at the Universidade Federal do Tocantins, Gurupi campus. Four bacterial strains were used, as follows: Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. The concentration of the extracts consisted of warm 10%, 20%, 20% heated and unheated tested in disk diffusion test, which is carried ratings 24 hours after application of the extract, the result is expressed in mm. The concentration of the aqueous extract of B. crassifolia were effective in inhibiting bacterial, except for E. coli. They were observed in color pigmentations roots characteristic of anthocyanin and quercetin, a condition that may have influenced the antimicrobial potential, the antibacterial action of these two natural flavonoids.
Keywords: Byrsonima crassifolia; antibacterial; sensitivity; roots